(untitled) (Development Service Industry Management, 2024)
The article examines the main approaches to determining innovation and investment security of both the national economy and business structures. The proposed definition of innovation and investment security of business structures. Emphasis is placed on the lack of an adequate level of innovation and investment security of Ukraine in modern conditions, unequivocal approaches to the evaluation of its indicators and a comprehensive assessment of the state of its formation in the country. The main criteria of innovation and investment security in crisis conditions are defined. Prospects for increasing the level of investment and innovation security of business structures are given. In the process of formation and strengthening of national economic security, an important place is occupied by the investment and innovation component, and the desire to ensure sustainable development of the economy based on an innovative model requires increasing the amount of investment resources, which must necessarily be included in the strategic priorities of the economic policy of Ukraine. One of the components of ensuring the sustainable development of the economy of Ukraine is the state of innovation and investment security, which must be formed in an end-to-end manner throughout the entire economic system, including the level of business structures.